Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1029/2021jb022011
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Intensity Decrease During the Second Half of the First Millennium BCE in Central Asia and Global Implications

Abstract: The geomagnetic field measured at the Earth's surface is the result of various sources. The main field, generated in the outer core, has changed over time at different time scales, varying from years (geomagnetic jerks)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 74 publications
(137 reference statements)
1
8
0
Order By: Relevance
“…In our previous study (Bonilla-Alba et al, 2021), we already suggested that the V-shaped intensity feature may have originated from a non-dipole contribution of the geomagnetic field. The new intensity data acquired here further corroborate this V-shaped pattern and contribute to a refined definition of the increasing branch by revealing high intensities at the end of the second century CE.…”
Section: Evidences Of a Non-dipole Field Contribution In Central Asia...mentioning
confidence: 84%
See 4 more Smart Citations
“…In our previous study (Bonilla-Alba et al, 2021), we already suggested that the V-shaped intensity feature may have originated from a non-dipole contribution of the geomagnetic field. The new intensity data acquired here further corroborate this V-shaped pattern and contribute to a refined definition of the increasing branch by revealing high intensities at the end of the second century CE.…”
Section: Evidences Of a Non-dipole Field Contribution In Central Asia...mentioning
confidence: 84%
“…Based on the preceding description, our primary focus now centers on geomagnetic field changes within the time frame spanning from 400 BCE to 400 CE, where the most important differences between robust data and models are observed. For the following discussion we considered the new data obtained here along with the data obtained in our previous study (Bonilla-Alba et al, 2021). Any previous data that do not meet modern standards of quality (represented by gray dots in Figure 5) have been excluded from our interpretation.…”
Section: First Full-vector Archeomagnetic Data From Central Asia: Com...mentioning
confidence: 99%
See 3 more Smart Citations